1814 Terr. of Miss. Laws 16, An Act To Authorize The Governor Of Mississippi Territory, To Accept Of The Services Of Citizens Exempted From Militia Duty, § 2 - (:unkn) unknown (General Publisher, 1814)
Immediately on the governor’s acceptance of any number of volunteers, by virtue of this act, each private shall proceed to provide himself with a good rifle, musket or shot gun with four flints, twenty rounds of powder, ball, or buckshot, best suited to his gun, together with the most convenient accoutrements. The commissioned officers shall be armed with swords; and the arms and accoutrements of all such volunteers shall be exempted from executions in payment of debts and their persons, when on service, free from arrest in civil cases.
--
Keywords: ARMED FORCES